Household food insecurity is associated with asthma control in Peruvian children living in a resource-poor setting. (1st December 2020) - Tarazona-Meza, Carla E.; Nicholson, Andrew; Romero, Karina M.; Pollard, Suzanne L.; Gálvez-Davila, Rocio M.; Hansel, Nadia N.; Checkley, William
Abstract: Rationale: Prior evidence suggests that there may be an association between asthma and food insecurity. We sought to describe the prevalence of food insecurity access, defined as having sufficient resources for appropriate foods in Lima, Peru, and evaluate its association with asthma status and control. Methods: We analyzed data from 553 children with asthma and 268 healthy controls aged nine to 19 years living in two peri-urban communities in Lima, Peru, in 2013. We used the Household Food Insecurity Access Scale to assess food insecurity. We defined uncontrolled asthma as an asthma control test score ≤19. We used multivariable logistic regressions to determine the relationship between asthma outcomes and food insecurity adjusting for age, sex, socioeconomic status, body mass index, and setting. Results: Average age was 14.2 years (SD 2.7). There was a high prevalence of household food insecurity in our study: 330 participants (40.2%) were food insecure, and average food insecurity access score was 2.7 points (SD 4.2). While being food insecure was not associated with asthma status (OR = 1.23, 95% CI 0.85 to 1.79; p = 0.28), it was associated with a higher odds of having uncontrolled asthma (OR = 2.01, 95% CI 1.13 to 3.59; p = 0.02). Each one-unit increase in food insecurity score (higher scores indicating more insecurity) was associated with 8% higher odds of having uncontrolled asthma (OR = 1.08, 95% CI 1.02 to 1.14; p < 0.01). Conclusions: Worse asthma control was associated with food insecurity. Future studies are needed to better understand the role of food security in determining the success of treatment strategies.